Tolvaptan rescue contrast-induced acute kidney injury: A case report. Issue 17 (April 2018) - Lee, Wei-Chieh; Fang, Hsiu-Yu; Fang, Chih-Yuan
Abstract: Rationale: Contrast-induced acute kidney injury is one of the most serious adverse effects of contrast media and is related to three distinct but interacting mechanisms: medullary ischemia, formation of reactive oxygen species and direct tubular cell toxicity, especially in the patients with chronic kidney disease. The strategies of treatment, including stabilization of hemodynamic parameters and maintenance of normal fluid and electrolyte balance, were similar to the management of other types of acute kidney injury. Patient concerns: A 58-year-old woman experienced acute oligouria after complex percutaneous coronary intervention for multiple vessel coronary artery disease. Diagnoses: Chest radiography showed pulmonary congestion and hyponatremia was noted after fluid hydration for suspicious contrast-induced nephropathy. Interventions: Oral tolvaptan, at 15mg per day, was used for three days. Outcomes: Urine output increased gradually and symptoms relieved one day later after using tolvaptan. Serum creatinine also improved to baseline level one week later after this event. Lessons: Here, we reported an interesting case about contrast-induced acute kidney injury and hypervolemic hyponatremia, where tolvaptan was used to rescue the oliguric phase. Tolvaptan could be considered to use for contrast-induced acute kidney injury and had possibility of prevention from hemodialysis. Larger studies are still needed to investigate the role of tolvaptan in rescuing the oliguric phase in contrast-induced acute kidney injury.